RELATIONSHIP KNOWLEDGE OF DIABETIC FOOT CARE WITH THE OCCURRENCE DIABETIC ULCER IN PUSKESMAS TEGUHAN - Ayu Indrianisa, Sukma; Nisa, Raudhotun (Journal of Vocational Nursing, 2020)
Introduction: Diabetes mellitus is a condition in which the body is unable to produce insulin so hyperglycemic. Uncontrolled hyperglikemi can result in several complications, one of which occurs in diabolical ulcers or leg injuries. Prevention of diasecond ulcers can be done by controlling blood sugar levels, exercising, and undergoing foot care. Knowledge of foot care needs to be known by diabetics in order to minimize the risk of diabetic ulcers. The purpose of this study is to know the level of knowledge of foot care in diabetics mellitus with the occurrence of diabetic ulcers. The design used is a scriptive correlation with the cross sectional approach. Methods: The technique of taking sambel with accidental sempling with a sample of 73 respondents. Analyze data using chi square. Results: The results of the study obtained as many as 40 reseponden (55.8%) knowledgeable and 50 respondents (68.5%) did not have a diabetikum ulcer. The results of the chi square analysis test obtained Pvalue = 0,000 which showed that there is a link between the knowledge of foot care and the incidence of diabetic ulcers in diabetics mellitus. Conclusion: From the results of this study, diabetics are expected to perform foot treatment so as to reduce the risk of diabetic ulcers.